2011
DOI: 10.1007/s11748-010-0743-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular oncology of lung cancer

Abstract: Progress in genetic engineering has made it possible to elucidate the molecular biological abnormalities in lung cancer. Mutations in KRAS and P53 genes, loss of specific alleles, and DNA methylation of the tumor suppressor genes were the major abnormalities investigated between 1980 and the 2000s. In 2004, mutations in the epidermal growth factor receptor (EGFR) gene that cause oncogene addiction were discovered in non-small-cell lung cancers (NSCLCs), especially in adenocarcinomas. Because they are strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 86 publications
0
41
0
6
Order By: Relevance
“…Of note, the profile of molecular alterations is quite different among the histological subtypes of lung cancer [6][7][8]. For example, epidermal growth factor receptor (EGFR) mutations [9], K-ras mutations and P16 methylation [8] are frequently found in non-small cell lung cancer (NSCLC), but not in SCLC [10]. In contrast, TP53 mutations [8,11] or RASSF1A methylation [12] is frequently found in SCLC, compared with NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the profile of molecular alterations is quite different among the histological subtypes of lung cancer [6][7][8]. For example, epidermal growth factor receptor (EGFR) mutations [9], K-ras mutations and P16 methylation [8] are frequently found in non-small cell lung cancer (NSCLC), but not in SCLC [10]. In contrast, TP53 mutations [8,11] or RASSF1A methylation [12] is frequently found in SCLC, compared with NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…EGFR, a gene that is frequently overexpressed in 40-80% of NSCLC cases, serves an important role in tumor cell survival and proliferation (16,17). Recent clinical trials with EGFR inhibitors have demonstrated positive results in patients with NSCLC, particularly by increasing the progression-free survival (PFS) time among patients harboring EGFR mutations compared with patients with wild-type EGFR (7-12).…”
Section: Discussionmentioning
confidence: 99%
“…Va rious molecules are being investigated as putative markers of CSCs in malignancies including lung cancer [5]. CD133, which was initially described as a surface antigen specific for human hematopoietic stem cells [6,7], is now being used to identify and isolate putative CSC populations from malignant tumors including cancers of the brain, prostate, liver, pancreas, and colon as well as melanomas [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%